The Effectiveness of Academic Buoyancy Training on Emotional, Social, and Educational Adaptation in Geography Students at the Martyrs of Mecca Campus of Farhangian University - Fooladi, Asma; Sadeghinia, Alireza; Arabsalari, Zahra (International Journal of Education and Cognitive Sciences, 2022)
Considering the importance of adaptation, especially in students of Farhangian University, the present study aimed to determine the effectiveness of academic buoyancy training on emotional, social, and educational adaptation in geography students of the Martyrs of Mecca campus. This research was applied in terms of objective and quasi-experimental in method, with a pre-test and post-test design along with a control group. The study population consisted of geography students at the Martyrs of Mecca campus of Farhangian University in Tehran for the academic year 2023-2024. Forty students were selected as the sample using a convenience sampling method and randomly placed into two groups of 20. The experimental group underwent 12 sessions of 70-minute academic buoyancy training, while the control group received no such training during this period. The data collection tools included a demographic information form and the Sinha and Singh (1993) Adaptation Inventory, and the data obtained from their implementation were analyzed using Multivariate Analysis of Covariance in SPSS software version 25. The results showed that academic buoyancy training led to a decrease in scores (improvement) of emotional, social, and educational adaptation in geography students of the Martyrs of Mecca campus (P < 0.001). The findings of this study indicate the effectiveness of academic buoyancy training in improving emotional, social, and educational adaptation in students. Therefore, academic buoyancy training can be utilized alongside other educational methods to enhance student adaptation.